Recent variability of the global ocean carbon sink - Landschuetzer, P.; Gruber, N.; Bakker, D. C. E.; Schuster, U. (Global Biogeochemical Cycles, 2014)
We present a new observation-based estimate of the global oceanic carbon dioxide (CO2) sink and its temporal variation on a monthly basis from 1998 through 2011 and at a spatial resolution of 1 degrees x1 degrees. This sink estimate rests upon a neural network-based mapping of global surface ocean observations of the partial pressure of CO2 (pCO(2)) from the Surface Ocean CO2 Atlas database. The resulting pCO(2) has small biases when evaluated against independent observations in the different ocean basins, but larger randomly distributed differences exist particularly in high latitudes. The seasonal climatology of our neural network-based product agrees overall well with the Takahashi et al. (2009) climatology, although our product produces a stronger seasonal cycle at high latitudes. From our global pCO(2) product, we compute a mean net global ocean (excluding the Arctic Ocean and coastal regions) CO2 uptake flux of -1.42 0.53 Pg C yr(-1), which is in good agreement with ocean inversion-based estimates. Our data indicate a moderate level of interannual variability in the ocean carbon sink (0.12 Pg C yr(-1), 1 sigma) from 1998 through 2011, mostly originating from the equatorial Pacific Ocean, and associated with the El Nino-Southern Oscillation. Accounting for steady state riverine and Arctic Ocean carbon fluxes our estimate further implies a mean anthropogenic CO2 uptake of -1.99 0.59 Pg C yr(-1) over the analysis period. From this estimate plus the most recent estimates for fossil fuel emissions and atmospheric CO2 accumulation, we infer a mean global land sink of -2.82 0.85 Pg C yr(-1) over the 1998 through 2011 period with strong interannual variation.